The effect of plyometric training on physical performance characteristics and race times in young female 800-m runners - Karahan, M.; Elmas, L.; Ünlü, H. (Science & Sports, 2024)
Objectives Although plyometric exercises are one of the best training methods with proven effectiveness in different sports, especially in improving physical performance, no study of young women running 800 m has been found. Therefore, this study examines the effects of plyometric exercises included in the traditional training program on the physical performance and race time of 800-m young female runners.